Bioethics: An interdisciplinary enterprise - Silber, T. J. (Journal of religion and health, 1982)
This paper offers a definition of bioethics and its implication. This is followed by a brief history of medical ethics and a description of the relationship established between bioethics, medicine, and other disciplines. It concludes with the author's presentation of his ideas on bioethics and interdisciplinary specialization, the result of his participation in the design and execution of a program of special studies in bioethics.